Possible observation of highly itinerant quantum magnetic monopoles in the frustrated pyrochlore Yb2Ti2O7 - Y. Tokiwa (Nature Portfolio, 2016)
Spin excitations above the ground state of spin ices, geometrically frustrated pyrochlore magnets, are equivalent to pairs of oppositely charged deconfined magnetic monopoles which may propagate through the system. Here, the authors evidence highly itinerant quantum magnetic monopole excitations in Yb2Ti2O7.